Deterministic and probabilistic approaches for corrosion in RC structures: A direct proposed model to total service life predictions - Nogueira, Caio Gorla [UNESP]; Yoshio, Lucas [UNESP]; Zacchei, Enrico (Elsevier, 2023)
In this paper the negative effects of the chloride ions attack in reinforced concrete (RC) elements have been studied. For this the vertical and horizontal chloride diffusivity has been treated by several models to identify the more relevant factor affecting the chloride concentration. The pitting corrosion has been treated to define the resistance losses of the shear forces and bending moments. An alternative deterministic/probabilistic procedure, by a direct and systematic new model, has been proposed to estimate the total time of service life for RC elements at the design phase. Several detailing configurations of steel bars in a RC beam, water/cement ratio and level of aggressiveness have been analysed to compare the model predictions. In this sense, this paper should provide useful results for analysts in terms of probability of failure for resistance losses and time of corrosion initiation. The goal is not only to provide practical results but also to evaluate the issue in a more modern risk analysis throughout the proposed prediction model.
Keywords: Chloride diffusion; Pitting corrosion; Reliability analysis; Resistance losses; Risk analysis; Total time of service life